MAB21L1 loss of function causes a syndromic neurodevelopmental disorder with distinctive cerebellar, ocular, craniofacial and genital features (COFG syndrome). Issue 5 (28th November 2018) - Rad, Abolfazl; Altunoglu, Umut; Miller, Rebecca; Maroofian, Reza; James, Kiely N; Çağlayan, Ahmet Okay; Najafi, Maryam; Stanley, Valentina; Boustany, Rose-Mary; Yeşil, Gözde; Sahebzamani, Afsaneh; Ercan-Sencicek, Gülhan; et al.
Abstract : Background: Putative nucleotidyltransferase MAB21L1 is a member of an evolutionarily well-conserved family of the male abnormal 21 (MAB21)-like proteins. Little is known about the biochemical function of the protein; however, prior studies have shown essential roles for several aspects of embryonic development including the eye, midbrain, neural tube and reproductive organs. Objective: A homozygous truncating variant in MAB21L1 has recently been described in a male affected by intellectual disability, scrotal agenesis, ophthalmological anomalies, cerebellar hypoplasia and facial dysmorphism. We employed a combination of exome sequencing and homozygosity mapping to identify the underlying genetic cause in subjects with similar phenotypic features descending from five unrelated consanguineous families. Results: We identified four homozygous MAB21L1 loss of function variants (p.Glu281fs*20, p.Arg287Glufs*14 p.Tyr280* and p.Ser93Serfs*48) and one missense variant (p.Gln233Pro) in 10 affected individuals from 5 consanguineous families with a distinctive autosomal recessive neurodevelopmental syndrome. Cardinal features of this syndrome include a characteristic facial gestalt, corneal dystrophy, hairy nipples, underdeveloped labioscrotal folds and scrotum/scrotal agenesis as well as cerebellar hypoplasia with ataxia and variable microcephaly. Conclusion: This report defines an ultrarare but clinically recognisable Cerebello-Oculo-Facio-Genital syndrome associated with recessive MAB21L1 variants. Additionally, our findings further support the critical role of MAB21L1 in cerebellum, lens, genitalia and as craniofacial morphogenesis.